"La Hija del Mar" and its Projection in the Mediterranean Sea - Nafría Fernández, María Jesús (Madrygal. Revista de Estudios Gallegos, 2015)
There are numerous literary references to the “hijas del mar”, lamias or sirens in the Iberian Peninsula. In this article, we will analyse the novel entitled La Hija del Mar by Rosalia de Castro, comparing it with the novel entitled La Filla del Mar, by Angel Guimera and a short story by Maria Bell Lloc. We will define the common features that describe the main characters.
Keywords: Rosalía de Castro; Ángel Guimerá; Maria de Bell Lloc; daughter of the sea (siren)